Dimensions of Vaccination Attitudes in Nigeria: A Study of the Impacts of COVID-19 Vaccine Risk Perception and Acceptance - Lawal, Abiodun Musbau; Olawa, Babatola Dominic; Odoh, Ikenna Maximillian; Olawole, Ayodeji Olorunfemi; Ajayi, Olubukola; Azikiwe, Judith Chineye; Ayodele, Israel Oluwatosin; Odusina, Emmanuel Kolawole; Attah, Thomas; Odedokun, Ezekiel Adeyemi; Babatunde, Stephen Ishola; Oladejo, Teslim Alabi; Otoghile, Confidence Chioma; Saka, Saheed Abiola (UI Scholars Hub, 2023)
Nigeria has been affected by the COVID-19 pandemic, and vaccination is a key strategy. However, the country faces vaccination hesitancy, poor risk perception, and low acceptance. This study aimed to assess the direct and interactive impacts of COVID-19 vaccine risk perception and acceptability on COVID-19 vaccination attitudes in the general Nigerian population. In a cross-sectional approach, participants completed a structured questionnaire including demographics, COVID-19 vaccine risk perception, acceptance, and vaccination attitude from April 2-30, 2021. The sample included 1,026 participants from different ethnicities across four regions (Southwest, South, Southeast, and North Central) in Nigeria, which were selected using the convenience sampling method. Multivariate analysis of variance results showed that the COVID-19 vaccine’s risk perception and acceptability have separate and interactive effects on overall vaccination attitudes. Interactively, individuals with high-risk perceptions and low acceptance expressed more skepticism about its benefits, were concerned about its long-term body effects, believed more in its commercialization, and preferred natural immunity. Nigerians’ apprehension about COVID-19 vaccination is impacted by their high-risk perception and low vaccine uptake.